Understanding the Concept of Job Satisfaction, Measurements, Theories and its Significance in the Recent Organizational Environment: A Theoretical Framework - Ali, Wasif (Archives of Business Research, 2016)
Job or work is an important aspect of an individual’s life and it occupies a lot of personal and professional time compared to any other activity. Satisfaction is the pleasure felt after a need is fulfilled. One would suppose a person is satisfied when his or her expectations or desires or requirements have been met. Job satisfaction describes how much extent an individual is pleased, comfortable or satisfied with his or her job. It is a pleasurable or positive emotional state resulting from the appraisal of one’s job or job experiences. In current organisations Job Satisfaction is a crucial subject of attention which is very considered by the higher authorities, policy makers and top executives because this issue is related to many other significant and important issues of organisations. Employees are the core assets and key part of any organisations by which all means of production are handled. As a human being this is human nature that employee are satisfied or dissatisfied what work they are assigned. This is the prime objective of the organizations that they should make and implement such type of policies that can make an employee to satisfy with his/her job which is assigned to them. It is clear from previous studies that how Job Satisfaction is important for any organisations. It is very important issue nowadays when organizations are facing with many types of employee related problems and challenges i.e. organizational performance, organizational commitment, employee turnover, employee productivity etc. Keeping in view the significance and importance of Job Satisfaction in organizations, scholar had endeavored to elaborate the construct of Job Satisfaction, its measurements, theories and its significance in current organizational issues. The research paper is theoretical in nature and subjects have been clarifies with the help of concerned literatures and previous studies regarding this area.